Numerical and experimental study of gaseous fuel injection for CNG direct injection. (15th January 2015) - Choi, Mingi; Lee, Sanghoon; Park, Sungwook
Highlights: KIVA-3V Release 2 code was modified for gaseous fuel injection. PLIF method was used for experiments of gaseous fuel injection. Gaseous fuel injection model was predicted well a general tendency of gas fuel injection. From the results, gaseous fuel injection model has the reliability about gas fuel direct injection. Abstract: This paper describes numerical and experimental studies of gaseous fuel injection for CNG direct injection. To simulate the CNG direct injection, the injection sub-model was updated to include gaseous fuel injection methodology. The gaseous fuel injection methodology, which is similar to a liquid injection model, can be used in the KIVA-3V Release 2 code with some modifications. In addition, this model can be used to simulate gaseous fuel injection using a coarse mesh, which saves calculation time. The core region was defined as an inviscid region near the nozzle exit. The core length has an effect on the spray penetration where a longer core length results in longer spray penetration. The values of the turbulence kinetic energy, turbulence length scale, and turbulence kinetic energy dissipation rate were adjusted depending on the grid location since the RNG (re-normalization group) k – ε turbulence model is known to over-predict gas jet diffusion. Furthermore, a PLIF (planar laser induced fluorescence) method was used for the gaseous fuel injection experiments. Acetone was selected as a tracer and post-image processing was performed using MATLAB code. In this study, the simulation results of CNG injection were compared to experimental data. Through comparison of the spray tip penetration results to experimental measurements, the gaseous fuel injection model produced reliable results for gas fuel direct injection.